Influence of natural infection of Toxocara vitulorum on markers of oxidative stress in Indian buffalo calves - SARMA, K; SARAVANAN, M; MONDAL, D B; DE, U K; KUMAR, M (The Indian Journal of Animal Sciences, 2012)
Present study envisages the possible oxidant/antioxidant imbalance due to toxocariasis in naturally infected buffalo calves before and after initiation of therapy. Buffalo calves (9) naturally infected with Toxocara vitulorum were selected to analyze hematological parameters, oxidative stress indices, levels of nitric oxide (NO) and minerals, viz. zinc, copper and iron and compared with 9 healthy buffalo calves. Pronounced reduction in the values of hemoglobin, packed cell volume, total erythrocyte count and oxidative stress indices like reduced glutathione, catalase and glutathione-s-transferase were observed in infected calves. However, significantly augmented levels of erythrocytic lipid peroxidation and serum NO were observed in infected calves. Levels of Zn, Cu and Fe significantly dropped in infected calves. All the infected animals were recovered completely after treatment with piperazine hydrate (300 mg/kg b. wt. PO for 2 days). Significant improvement in hematological parameters and mineral status were observed but no statistically significant improvement with the oxidative stress indices were observed in post treated calves. Results denote that incorporation of antioxidants in the therapeutic regimen might be helpful to curb the oxidative stress in the course of toxocariasis in buffalo calves.